Exosomes from the tumor microenvironment as reciprocal regulators that enhance prostate cancer progression. (10th July 2016) - Liu, Che‐Ming; Hsieh, Chia‐Ling; Shen, Chia‐Ning; Lin, Cheng‐Chieh; Shigemura, Katsumi; Sung, Shian‐Ying
Abstract: Distant organ metastasis of prostate cancer is a puzzle, and various theories have successively arisen to explain the mechanism of lethal cancer progression. While perhaps agreeable to many cancer biologists, the very statement of "seed and soil" proposed by Stephan Paget in 1881 is arguably still the major statement for organ‐specific cancer metastasis. Since recent studies showed important correlations of regulation of cancer cells and the microenvironment, exosomes from cancer and stromal cells seem to create another important niche for metastasis. Stromal cells pretreated with exosomes from metastatic cancer cells increase the potential of change stromal cells. The poorly metastatic cancer cells could also enhance malignancy through transfer of proteins, microribonucleic acid and messenger ribonucleic acid to recipient cancer cells. Herein, we reviewed extracellular exosomes as a factor involved in cross‐talk between stromal and prostate cancer epithelial cells.